The feasibility of a multi‐professional training to improve how health care professionals deliver different news to families during pregnancy and at birth. (16th February 2020) - Mugweni, Esther; Lowenhoff, Catherine; Walker, Melita; Jaswal, Sabrena; Emrys‐Jones, Angela; Adams, Cheryll; Kendall, Sally
Abstract: Background: In the United Kingdom, pregnant women are offered foetal anomaly screening to assess the chance of their baby being born with eleven different conditions. How health care professionals (HCPs) deliver news about a child having a congenital anomaly affects how it is received and processed by parents. We refer to this news as different news. Methods: We conducted a mixed methods evaluation of a training intervention to improve how HCPs deliver different news. Twenty‐six HCPs self‐completed pretraining and posttraining questionnaires on skills, knowledge, and attitudes related to delivering different news. Qualitative interviews were conducted with eight HCPs. Quantitative data were analysed using descriptive statistics, the paired t test to compare the pre and post scores and estimate the difference between pre and post scores, and the 95% confidence interval. Qualitative data were analysed using framework analysis guided by the Theoretical Domains Framework (TDF). Results: The training intervention was both feasible and acceptable. HCPs indicated that it enhanced or consolidated their knowledge and skills, covered topics relevant to their practice, and that they would recommend it to colleagues. Participants particularly valued integration of the voice of parents with lived experience in the training. Significant increase in mean scores were observed in confidence to deliver different news (2.81, 95% CI [2.43, 3.19] to 4.28, 95% CI [4.09, 4.47]; p < .001) and skills to deliver different news (3.00, 95% CI [2.64, 3.36] to 4.36, 95% CI [4.13, 4.59]; p < .001). HCPs reported feeling more confident in their ability to provide sensitive, responsive, balanced care to families. Conclusions: The significant improvements in confidence and skills reported by HCPs suggest that the training may be effective in equipping HCPs to minimize the distress, anxiety, and depression associated with receiving different news. This represents a key aspect of the prevention of mental ill health across the life course.